Association between disordered eating and body weight status among adolescents in Kuala Lumpur, Malaysia - V. Sanker, Kaartina; Chin, Yit Siew; Rezali, Fara Wahida; Woon, Fui Chee; Mohd Shariff, Zalilah; Mohd Taib, Mohd Nasir (International Association for the Study of Obesity, 2014)
Overweight and disordered eating are major public health problems among adolescents due to the high prevalence and potential physical and psychological health consequences. This study aimed to determine the association between disordered eating behaviors and body weight status among adolescents in Kuala Lumpur, Malaysia. A cross-sectional multistage study was conducted in four selected schools in Kuala Lumpur. A total of 501 Malaysian adolescents (male: 42.0%; female: 58.0%) aged between 13–17 years completed the Eating Attitude Test-26 (EAT-26) which was used to screen adolescents who are at-risk of eating disorders and Three Factor Eating Questionnaire (TFEQ-R) was used to measure restrained eating, uncontrolled eating, and emotional eating. Body weight and height of the adolescents were measured. The prevalence of overweight and obesity (21.2%) was three times higher than the prevalence of thinness (7.2%) among adolescents. About one in five (24.4%) of the adolescents were at-risk of eating disorders, with the highest prevalence among obese adolescents (39.3%) followed by overweight (29.8%), normal weight (21.8%) and thin (20.0%) adolescents (X2 = 12.4, p < 0.05). Multiple linear regression analysis showed that adolescents with poor cognitive restraint on eating (R2 changed = 0.18, B = −0.154, p < 0.01) and greater tendency of emotional eating (R2 changed = 0.11, B = 0.075, p < 0.01) explained 29.0% of variances in the BMI-for-age model. In conclusion, disordered eating was prevalent in adolescents, particularly among overweight and obese adolescents. Intervening disordered eating problem should be included as one of the crucial components of overweight and obesity prevention program in adolescents.